Evictionism and Negative Homesteading - Wąsiak, Kacper (Studia z Historii Filozofii, 2025)
In “Evictionism: The Only Compromise Solution to the Abortion Controversy”, Walter Block defends a position in the abortion debate known as “evictionism”. According to this view, a woman has the right to evict a fetus from her body for whatever reason at any time she wishes during the pregnancy, provided it is done in the gentlest manner possible. In the present article, I analyze the relationship between evictionism and negative homesteading – another well-known theory proposed by Block. I argue that these two views are incompatible, i.e., that holding both simultaneously leads to contradiction. I also suggest a way to resolve this contradiction by presenting an argument against negative homesteading.